2018
DOI: 10.1111/acer.13757
|View full text |Cite
|
Sign up to set email alerts
|

Regional Brain Volume Changes in Alcohol‐Dependent Individuals During Short‐Term and Long‐Term Abstinence

Abstract: Results showed significant volume reductions in key regions of the executive control, salience, and emotion networks in ALC at entry into treatment and significant volume increases during short-term and long-term abstinence that were nonlinear over the entire abstinence period for the DLPFC, OFC, and insula. This gray matter plasticity during alcohol abstinence may have important neurobiological and neurocognitive implications in ALC, and it may contribute to an individual's ability to maintain abstinence from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 60 publications
7
43
0
Order By: Relevance
“…Taken together in the context of the PTSD and AUD literature, our current findings may reflect that smaller volumes across dorsal and rostral ACC could have implications for the effective management of negative mood states and stress triggers in those with both PTSD and AUD. This hypothesis is consistent with evidence that smaller volumes of the dorsal ACC across a range of psychopathologies is related to poorer executive functioning (Goodkind et al, 2015), and that recovery in AUD is also related to rostral and dorsal ACC volume increases with abstinence (Zou et al, 2018). However, Helpman et al, 2016 also found volume decreases in rostral ACC following treatment for PTSD, suggesting the relationship may not be the same across subregions of the ACC, stages of illness, or within PTSD alone compared to PTSD in the context of AUD (Seo et al, 2013; Wilcox et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Taken together in the context of the PTSD and AUD literature, our current findings may reflect that smaller volumes across dorsal and rostral ACC could have implications for the effective management of negative mood states and stress triggers in those with both PTSD and AUD. This hypothesis is consistent with evidence that smaller volumes of the dorsal ACC across a range of psychopathologies is related to poorer executive functioning (Goodkind et al, 2015), and that recovery in AUD is also related to rostral and dorsal ACC volume increases with abstinence (Zou et al, 2018). However, Helpman et al, 2016 also found volume decreases in rostral ACC following treatment for PTSD, suggesting the relationship may not be the same across subregions of the ACC, stages of illness, or within PTSD alone compared to PTSD in the context of AUD (Seo et al, 2013; Wilcox et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Early age of regular drinking onset in the AUD group compared to controls in the present study (Table 1) also supports the conclusion of alcohol use in adolescents affecting cortical volume in these regions in the Pfefferbaum et al (2018) study. Orbitofrontal cortical volume is reportedly affected by Wernicke’s Korsakoff Syndrome (WKS) and the propensity to relapse following abstinence and older age are reported to be related to pronounced orbitofrontal atrophy in uncomplicated AUD (Beck et al, 2012, Durazzo et al, 2011, Zou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the most recent longitudinal neuroimaging studies on AUD allow to raise preliminary hypotheses on which brain areas are specifically affected by current alcohol consumption (CAC) or duration of alcohol use disorder (DAD). These studies revealed that there is a partial though substantial structural recovery of almost all brain regions in the months following alcohol withdrawal, except the amygdala . This suggests that brain alterations in this later region could reflect a cumulative toxicity of alcohol over time, ie, being possibly related to DAD.…”
Section: Introductionmentioning
confidence: 89%
“…Some alterations could be the expression of vulnerability markers for AUD, being independent of alcohol neurotoxicity and thus quite stable, whereas other alterations might reflect some temporary or fixed effects of alcohol on the brain or of the overall addiction process. In this respect, some of the structural alterations found in AUD appear to regress quickly after cessation of alcohol use . Specifically, it was found that high prewithdrawal drinking levels were associated with a faster and more important regression of structural alterations, suggesting that some brain alterations could result from immediate alcohol neurotoxicity and might thus be merely related to the recent amounts of alcohol used.…”
Section: Introductionmentioning
confidence: 99%